Analisis Pelanggaran Etika Profesi Akuntansi (Studi Skandal Jiwasraya Indonesia) Manipulasi Laporan Keuangan - Yosua Yosua; Yuli Rofiyani; Muflikhatun Novia Rahwawati; Delia Hanin Salsabila; Saridawati Saridawati (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the violation of accounting professional ethics in the PT Asuransi Jiwasraya scandal, one of the biggest financial cases in Indonesia. The main focus of this study is to identify the forms of ethical violations that occur, analyze the principles of the code of ethics that are violated, and understand the impact and causal factors of manipulative actions in the company's financial statements. This study uses a descriptive qualitative approach based on the theory of Accounting Professional Ethics and Fraud Triangle Theory. The results of the analysis show that in the Jiwasraya case there was a violation of the principles of integrity, objectivity, professional competence, confidentiality, and professional behavior. Manipulation of financial statements was carried out to cover up the company's actual loss, which caused state losses of up to trillions of rupiah and damaged public trust in the financial industry. Stricter supervision, consistent application of professional ethics, and improvement of governance are needed so that similar cases do not recur in the future.